Strategi Peningkatan Kualitas Pendidikan Pesantren Melalui Pengembangan Program Pesantren Ramah Anak - Albert, Albert; Sesmiarni, Zulfani (Jurnal Pendidikan Indonesia, 2022)
The quality of education is a pillar of human resource development which is very important for national development. The Child Friendly Pesantren Program (PRA) is one of the efforts made to improve the quality of Islamic boarding school education. This research is important because so far the quality of pesantren education has only been studied on aspects of learning related to the academic field which have an impact on certain aspects. The purpose of this study was to identify and understand the strategy for improving the quality of education at the Serambi Mekkah Integrated Islamic Boarding School through the child-friendly pesantren program. In addition, to find out the impact or implications of implementing a child-friendly pesantren program on the quality of education. This study uses a descriptive qualitative approach with a case study design. Data collection techniques were carried out by means of in-depth interviews, participant observation, and documentation. Data analysis was carried out by means of data collection, data coding, data classification, data reduction, and data exposure. The results showed that the strategy carried out included several stages, namely: Formation of a child-friendly boarding school implementing team, conducting program socialization, human resource development (teachers and staff), Building collaboration, Fulfilling indicators for child-friendly pesantren components, Implementing a monitoring and evaluation process, and Responsive to inputs for improving child-friendly school programs. The program's implications for the quality of education can be seen in three aspects, namely teachers, students and institutions.